Математическое моделирование равновесного состава системы BaS–Ba(HS)₂–H₂S–H₂O - Цейтлин, Моисей Абрамович; Райко, Валентина Федоровна (Національний технічний університет України "Київський політехнічний інститут імені Ігоря Сікорського", 2018)
Разработана математическая модель, описывающая равновесный состав системы BaS–Ba(HS)₂–H₂S–H₂О, позволяющая, в частности, рассчитывать рН раствора. Модель использована для расчета движущей силы десорбции сероводорода в процессе получения карбоната бария.

A mathematical model describing the equilibrium composition of the BaS–Ba(HS)₂–H₂S–H₂О system is developed. Model allows, in particular, to calculate the pH of the solution, and was used to calculate the driving force for desorption of hydrogen sulfide in the process of obtaining barium carbonate.
Mathematical modeling of the equilibrium composition in the system BaS–Ba(HS)₂–H₂S–H₂O
Keywords: математическая модель; равновесие; состав раствора; сульфид бария; сероводород; водородный показатель; mathematical model; equilibrium; composition of solution; barium sulfide; hydrogen sulfide; potential of hydrogen